Probing Radiosensitisers in Electron Transfer Experiments - Mendes, Mónica Filipa dos Santos (2019)
The impact of ionising radiation in the living systems is being investigated for decades, because its capability to induce damage in tissues and cells, compromising the DNA molecule integrity, resulting in mutations and eventually cells death. Considering this, ionising radiation can be very useful in different fields, especially in radiation therapy. However, it is necessary to guarantee that the effects of radiation in normal tissues during a radiation treatment are minimised. Many efforts have been made to improve the radiotherapy protocols, namely by the application of radiosensitisers which enhance the effect of radiation. Recent research investigations have demonstrated the role of secondary low-energy electrons as the main damaging agents in DNA. These secondary electrons can interact directly or indirectly with molecules, producing highly reactive species (ions and radicals). Moreover, it is also known that electrons do not exist freely in the physiological medium, but rather in solvated and/or in pre-solvated states. Therefore, studies on electron transfer between atoms/ions and biomolecules seems crucial to better understand the molecular mechanism of radiation interaction. The work presented in this thesis consists on the study of electron transfer collisions of atoms/ions in molecules of biological relevance. Initially, neutral potassium collisions in imidazole, nitroimidazoles (4-nitroimidazole and 2-nitroimidazole) and methylated compounds (1-methyl-4-nitroimidazole and 1-methyl-5-nitroimidazole) were investigated by time-of-flight (TOF) mass spectrometry in a crossed beam experiment comprising a neutral potassium beam and a molecular effusive beam. In these experiments the anionic fragmentation patterns and yields were obtained. These results present some differences from the dissociative electron attachment (free electrons) results, highlighting the importance of charge transfer studies in understanding the molecular reactions upon radiation. The second part of the work was performed in a novel crossed beam setup where collisions between oxygen anions and molecules as nitrogen, water and pyridine were investigated by measuring positive and negative fragmentation patterns through TOF mass spectrometry. From these studies we obtained for the first time experimental electron detachment cross-section of O2− in water and pyridine.